APLIKASI PRESENSI KARYAWAN KLINIK MITRAMEDIK SUKAMANAH BERBASIS WEB - Aridzal Ridwan; Novita Anggraini (Melati Institute, 2023)
As of right now, the world has entered a digital era thanks to the advancement of information technology and computerization. Information systems in the area of web applications are also still expanding. This study was carried out at the MITRAMEDIK SUKAMANAH CLINIC. The goal of this project is to create an employee attendance system that can be improved or changed from a manual to a technological system utilizing a web-based application. In this study, observation, interviews, and literature reviews were used as data collection methods. The research's findings are then examined using descriptive methods and action research, a research approach that aims to characterize and interpret research objects in terms of the activities and data manipulation they take. The existing clinical employee attendance system is less effective and efficient, and since it is still manual, it has to be changed or improved utilizing technology, according to the study's findings.